Mapping ethical issues encompassing end-of-life care for persons experiencing severe and persistent mental illness: a qualitative study - Loïc Moureau; Monica Verhofstadt; Caressa Van Hoe; Joris Vandenberghe; Chantal Van Audenhove; Axel Liégeois (BMC Medical Ethics)
Abstract Background Persons experiencing severe and persistent mental illness (SPMI) represent a small but vulnerable group in mental health care and society. Research on this population is limited, despite significant ethical challenges in their care. These challenges include the severity of their illness, limited social networks, communication difficulties, impaired decision-making capacity, and, at times, disruptive behavior. Purpose This study aims to explore the ethical themes that emerge in the care of persons experiencing SPMI, both in general and at the end of life. Specifically, we examine which issues arise, how care teams address ethical dilemmas, who is involved in decision-making, and what ethical frameworks or practices are utilized. Methods We conducted 73 in-depth qualitative interviews with care users, family members, caregivers, care managers, and experts from the Flemish region of Belgium. The data were analyzed through content analysis to identify recurring themes and reflect on ethical practices. Results The findings reveal that while many facilities have ethical guidelines or advisory structures such as ethics committees, these are often not well known or not perceived as easily accessible to frontline staff. Ethical dilemmas are predominantly addressed at the team level, with some organizations employing a reference person ethics in the unit, “ethics pubs”, or peer support mechanisms for challenging situations. The most frequently mentioned ethical issue was euthanasia, whereas others included neglect in home settings, prolonged delays in initiating palliative care, and maintaining autonomy for care users. Resource allocation, both at the organizational and societal levels, was also identified as an ethical concern. Caregivers described tensions between creative, individualized care and institutional policies, whereas families emphasized the shared responsibility in finding appropriate care. Conclusion Ethical care for persons experiencing SPMI demands attention to autonomy, collaboration, and resource distribution. Greater accessibility to ethical support systems and tailored approaches are needed to balance recovery-oriented care with a palliative care approach, ensuring dignity and respect for this vulnerable group. Clinical trial number Not applicable.